Rancang Bangun Sistem Informasi Baitulmal Berbasis Website Menggunakan Metode Service Oriented Architecture (SOA) - Kuncoro, Arsito Ari; Siswanto , Siswanto; Nugroho, Didik Setio (MEANS (Media Informasi Analisa dan Sistem), 2024)
Majelis Dzikir Tasbih Indonesia is an official legal organization for Indonesian Muslims who routinely perform the Sunnah Tasbih Prayer together. This organization has hundreds of thousands of members spread across all branches in Indonesia. As a large organization, Majelis Dzikir Tasbih Indonesia manages finances through contributions and zakat from all its members. However, financial management is still carried out conventionally by involving treasurers in each branch, who then report to the central treasurer every month using Microsoft Office Excel. This method makes it difficult to search for data in a certain period because the data is spread across various worksheets or separate files. In addition, the collection and distribution of zakat that is not properly recorded reduces the level of member trust in financial management. Based on these problems, this study aims to develop website-based information technology, namely the financial information system of Majelis Dzikir Tasbih Indonesia. This system is expected to help manage finances and disseminate information related to charity activities more widely, quickly, safely, in real time, and transparently. The Service Oriented Architecture (SOA) method will be used in the development of this system, because it offers benefits such as not being dependent on other functions (loose coupling), can be reused in various projects or situations without having to start from scratch (reusability), and can be integrated with various applications (service sharing).